The relationship between polycystic ovary syndrome and insulin resistance from 1983 to 2022: A bibliometric analysis - Chen, Tong; Yu, Yue; Jia, Fan; Luan, Peijie; Liu, Xinmin (Frontiers in Public Health, 2022)
Background: Polycystic ovary syndrome (PCOS) is a common clinical disease often associated with insulin resistance（IR）. The interaction between PCOS and IR will promote the progress of PCOS and the risk of related complications, harm women's physical and mental health and increase the social and economic burden. Materials and Methods: PCOS IR related literatures were retrieved through Web of Science Core Collection (WoSCC) Database, and imported into VOSViewer and CiteSpace respectively in plain text format to conduct the literatures visualization analysis of authors, countries, institutions, highly cited literatures and keywords, aiming to reveal the hot spots and trends of PCOS IR fields. Results: A total of 7,244 articles were retrieved from 1900 to 2022. Among them, the United States has made the largest contribution. Diamanti-Kandarakis E was the author with most publications, and University of Athens was the institution with most publications. Keyword analysis showed that PCOS interacts with IR mainly through sex-hormone binding globulin, luteinizing hormone, insulin-like growth factor, oxidative stress and other mechanisms. In addition, the complications of PCOS complicated with IR are also the focus of researchers' attention. Conclusions: Through bibliometric analysis, this paper obtains the research hotspot and trend of PCOS IR fields, which can provide reference for subsequent research.